If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z = 10 + -1y Solving z = 10 + -1y Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Simplifying z = 10 + -1y
| k-25%=9 | | k-25%=9 | | 6x+1=2x+4 | | 4p+3q=-31 | | -7(x+1)-17=33+6 | | k-25%=9 | | -3(4t-4)+6t=5t-8 | | 15x^3+72x^2-515=0 | | log(2x-18)=2 | | 0.03(6c-88)=-0.6(c-6) | | 3(20+6)=90 | | -0.9c=-63 | | 15x=4-x^2 | | -[4z-(15z+9)]=9+(10z+6) | | r^3-9r^2-81r+729=0 | | 0.4t=-44 | | r^2-8tw+4rw-8tw= | | 5y-25=55x | | b^3+18b^2+81b=0 | | 9(3)+4y=36 | | 15+(5.25*x)=46.50 | | Y+3.9=-6.6-7.7 | | (5)(3)-2x=3-4x | | 9(3)+3y=36 | | 2a-b=-7 | | 3w^2-365w+8550=0 | | 15t^2-13t-2=0 | | -5-11=7x+14-6x | | b^3+18b^2+812b=0 | | 4-6=y | | 4x+14-3x=-6-10 | | 3a-5b+5c+2a+3b-c= |